Comparative Analysis of Proteins Associated with 26S and 20S Proteasomes Isolated from Rabbit Brain and Liver - Buneeva, O. A.; Kopylov, A. T.; Zgoda, V. G.; Gnedenko, O. V.; Kaloshina, S. A.; Medvedeva, M. V.; Ivanov, A. S.; Medvedev, A. E. (Biochemistry (Moscow). Supplement. Series B, Biomedical chemistry, 2022)
The fractions of 26S and 20S proteasomes have been isolated from the rabbit liver and the brain. According to mass spectrometric (MS) analysis, the 26S proteasome fractions from these organs contained catalytic and regulatory subunits characteristic of the proteasome core and regulatory subunits. The 20S fractions of brain and liver proteasomes contained only catalytic proteasome subunits. In addition to the proteasome subunits, the isolated fractions contained components of the ubiquitin-proteasome system, ubiquitinated proteins, enzymes involved in various metabolic processes, cytoskeletal components, signaling, regulatory, and protective proteins, as well as proteins regulating gene expression, cell division, and differentiation. The abundance of a number of proteasome-associated proteins was comparable or exceeded the abundance of intrinsic proteasome components. About a third of the proteins common to all studied fractions (26S and 20S of brain and liver proteasomes) belong to the group of multifunctional proteins. Selective biosensor validation confirmed the affinity binding of proteins (aldolase, phosphoglycerate kinase) identified during MS analysis to the brain 20S proteasome. Comparison of the subproteomes of the 26S and 20S brain proteasomes showed that removal of components of the regulatory (19S) subparticles caused almost two-fold increase in the total number of individual proteins associated with the core part of the proteasome (20S). In the liver, the number of proteins associated with the core part of the proteasome remained basically unchanged after the removal of the components of the regulatory (19S) subparticles. This indicates that in the brain and, possibly, in other organs, proteins of the regulatory (19S) subunit play an important role in the formation of the proteasome interactome.